2017
DOI: 10.1002/ijc.30812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic variants in association with colorectal cancer risk and survival in Asians

Abstract: Genome-wide association studies (GWAS) have identified over 40 genetic loci associated with colorectal cancer (CRC) risk. The association of single nucleotide polymorphisms (SNPs) at these loci with CRC risk and survival has not been adequately evaluated in East Asians. GWAS-identified CRC risk variants were used to construct weighted genetic risk scores (GRSs). We evaluated these GRSs in association with CRC risk in 3,303 CRC cases and 3,553 controls using logistic regression models. Associations with overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…To date, a moderate number of CRC risk evaluation studies, including GWAS‐identified SNPs, have been reported, but their assessment models were constructed either using a single evaluation method or using only one population . Therefore, the present study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a moderate number of CRC risk evaluation studies, including GWAS‐identified SNPs, have been reported, but their assessment models were constructed either using a single evaluation method or using only one population . Therefore, the present study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous genome‐wide association studies (GWASs) have identified single nucleotide polymorphisms (SNPs) associated with CRC risk . However, few studies have explored the value of these SNPs in evaluating an individual's risk of CRC, particularly in Chinese populations . Therefore, we systematically analyzed 85 GWAS‐identified SNPs (Supporting Information Table S1) using three large‐scale GWAS datasets to determine the potential applications of genetic variants (Supporting Information Table S2).…”
Section: Introductionmentioning
confidence: 99%
“…Among previous studies on the role of colorectal cancer susceptibility SNPs in prognosis, several had constructed PRSs . Dai et al observed a cumulative effect for unfavorable genotypes in models including 2 SNPs (rs10749971 and rs961253) for recurrence and 3 SNP (rs961253, rs4464148, and rs6983267) for survival .…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al observed a cumulative effect for unfavorable genotypes in models including 2 SNPs (rs10749971 and rs961253) for recurrence and 3 SNP (rs961253, rs4464148, and rs6983267) for survival . In a survival analysis, Wang et al used a weighted PRS using 5 SNPs from a literature review (rs1321311, rs6983267, rs4939827, rs10411210, and rs961253) and the number of risk alleles in 2 SNPs (rs6983267 and rs1957636) and found that each SNP was associated with mortality with a linear trend . Phipps et al also observed that the sum of alleles for 3 SNPs (rs4939827, rs10795668, and rs4925386) was associated with survival .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation